Flavanols, proanthocyanidins and antioxidant activity changes during cocoa (Theobroma cacao L.) roasting as affected by temperature and time of processing. (1st May 2015) - Ioannone, F.; Di Mattia, C.D.; De Gregorio, M.; Sergi, M.; Serafini, M.; Sacchetti, G.
Highlights: Flavanols and proanthocyanidins degradation rates upon cocoa roasting were studied. Polyphenols degradation rate was strictly temperature dependent. High temperature-short time roasting processes minimised proanthocyanidins loss. Antioxidant activity changed upon roasting at different temperatures. Low temperature-long time roasting processes maximised chain-breaking activity. Abstract: The effect of roasting on the content of flavanols and proanthocyanidins and on the antioxidant activity of cocoa beans was investigated. Cocoa beans were roasted at three temperatures (125, 135 and 145 °C), for different times, to reach moisture contents of about 2 g 100 g −1 . Flavanols and proanthocyanidins were determined, and the antioxidant activity was tested by total phenolic index (TPI), ferric reducing antioxidant power (FRAP) and total radical trapping antioxidant parameter (TRAP) methods. The rates of flavanol and total proanthocyanidin loss increased with roasting temperatures. Moisture content of the roasted beans being equal, high temperature-short time processes minimised proanthocyanidins loss. Moisture content being equal, the average roasting temperature (135 °C) determined the highest TPI and FRAP values and the highest temperature (145 °C) determined the lowest TPI values. Moisture content being equal, low temperature-long time roasting processes maximised the chain-breaking activity, as determined by the TRAP method.